The Semiotics of Damascus City - Abou Assaf, Kawthar (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study seeks to analyze the symbolic content of Damascus as a city, applying the descriptive, analytical and semiotic methodology in order to decode its signifiers phenomenologically, transcending the apparent towards the thing in itself. The importance of the study lies in the desire to reach a different semiotic discourse, with clear terms and symbolic structure, along with the accumulated signs steeped in social origins, contrary to previous studies which saw in the city as only a realm of stones and humans, let alone buildings .The study also relied on analysis, contrary to previous interpretations, which focused on quantity rather than quality This study has concluded that the more spacious the pavement is the stronger the sense of citizenship will be, and vice versa. The pavement is a public sphere which hosts the citizen. However, the designer of the city and the violations of laws have established the power of the useful and discarded the aesthetics of the public sphere. Accordingly, the car is given more prominence in the public sphere than the humans. As for the advertisement and its several images, the advertiser seeks to construct a special building rich with expressive traits in order to convey a specific message capable of leaving an impact in terms of consumption and achieving quick and easy profits. تسعى هذه الدراسة للتوصل إلى المحتوى الدلالي لمدينة دمشق بالاعتماد على المنهج الوصفي والتحليلي السيميائي , بهدف التمكن من قراءتها قراءة فينومولوجيا تبحث عن الدلالة في الظاهر توسلا للشيء عينه . وتبرز أهمية الدارسة من خلال التوصل إلى خطاب سيميائي مختلف للمدينة له لغته الخاصة, ويشيد أنسجتها الرمزية وما تراكم فيها من علامات لها أصول اجتماعية بخلاف ما هو سائد في الأبحاث التي لا ترى في المدينة إلا بشرا و حجرا, وما شيد فيها من أبنية. واعتمد ت الدراسة على عناصر في التحليل بخلاف أيضا ما هو مألوف في الدراسات التي كانت مقارباتها أقرب إلى الكم منها إلى الكيف, فالحديث يصعب عن حياة مدينية من دون تناول حياة الناس في الرصيف وقراءة الصورة في الإشهار وما تبثه من رسائل, ومن دون السيارة أيضا يتغير المشهد الحضري. قسمنا الدراسة إلى قسمين نظري تضمن: تعريف السيمياء وخصائص العلامة عند سوسير و ثنائياته وبنية الصورة والفضاء الإشهاري وعملي تضمن: تحليل العلامة الأيقونية واللسانية للعناصرالتي اعتمدناها في التحليل بالاستناد إلى نظريات (فرديناند دوسيوسير) و(رولان بارت) و(أمبرتو إيكو).. وتوصلت الدراسة إلى أنه بقدر ما يتكثف الرصيف بقدر ما تتكثف معنى المواطنة, وبقدر ما يتقلص حيزه بقدر ما تتقلص قيمة المواطنة. الرصيف مجال عام يستوعب المواطن لكن مصمم المدينة و تجاوزات القوانين كرَّسا النفعي ولم يراعيا ما هو عام, وضمن هذه الفعالية الأداتية يسند إلى السيارة ما لا يسند إلى البشر في الحيز العام، أما في الإشهار وصوره يعمد المُعلن إلى إشادة بناء خاص تتضافر فيه مكوناته التعبيرية بقصد تبليغ رسالة محددة للتأثير بكل الوسائل لغاية الاستهلاك وتحقيق أرباح سريعة وسهلة .